Why do Post-Secondary Students Seek Counselling? - Cairns, Sharon L.; Massfeller, Helen F.; Deeth, Sander C. (Canadian Journal of Counselling and Psychotherapy, 2009)
The purpose of this study is to document reasons that Canadian postsecondary students seek counselling and to report counsellor ratings of the severity and complexity of presenting concerns. For over three academic years, counsellors at a large Canadian university completed a Presenting Issues Form on all clients (N = 2,943) following the initial session. The most frequent presenting issues were (a) relationship concerns, (b) anxiety/stress, (c) depression/grief, (d) academic, and (e) career. Global severity ratings indicated high degrees of distress. The severity of presenting concerns has implications for program development, policy development, and professional development of counsellors working in postsecondary institutions.